THE SIGNAL APPROACH TO MODELLING THE BALANCE OF PAYMENT CRISIS - O. Chernyak; B. Yakymchuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper considers and presents synthesis of theoretical models of balance of payment crisis and investigates the most effective ways to model the crisis in Ukraine. For mathematical formalization of balance of payment crisis, comparative analysis of the effectiveness of different calculation methods of Exchange Market Pressure Index was performed. A set of indicators that signal the growing likelihood of balance of payments crisis was defined using signal approach. With the help of minimization function thresholds indicators were selected, the crossing of which signalize increase in the probability of balance of payment crisis.